Evaluating alloy-718 machinability values modelling by using response surface methodology - AY, MUSTAFA (My University, 2022)
With the development of the manufacturing industry, machining parameters and material processing efficiency are important due to cost, sustainability, and other parameters, which are determining factors for usage width, material choice, and production rate. Machinability and optimization are among the scientists\" and industry workers\" timely objectives, guiding the manufacturing industries. Thus, the study and analysis of parameters such as surface roughness, tool wear, and force application in superalloy machining would be beneficial in various fields of the manufacturing industry. In this work, RSM (surface response method) modelling and analysis of relationship Fx, Fy, Fz forces between surface roughness of Inconel-718 material, which is a very unique alloy in terms of corrosion resistance, high-temperature elevation, and fatigue values, is examined. From this work, it was found that an experimental design was prepared using the Taguchi method, and the required number of measurements and parameter values were determined with a small number of experiments. Then, the most ideal values were determined using the Response Surface Methodology and ANOVA method to determine the best parameter levels after the surface roughness and cutting forces measurements.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Mühendislik (çeşitli); Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences; Alloy-718; Machinability; Taguchi method; Surface roughness; Cutting performance; INCONEL 718; OPTIMIZATION; ROUGHNESS; PARAMETERS